2022
DOI: 10.5937/jomb0-37514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of amino acid profile in serum of patients with Covid-19 for providing a new treatment strategy

Abstract: Objective: Amino acids have an important role in metabolism and may affect COVID-19-related outcomes. Our study, the amino acid serum level of hospitalized COVID-19 patients was evaluated for determining new treatment strategy. Methods: The amino acid profile covering 43 amino acids in 68 subjects, comprising 30 (14 men and 16 women) controls and 38 (16 men and 22 women) COVID-19 patients, were examined. In addition, the amino acid profiles of the participants were screened by LC-MS/MS. Results: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
2
12
1
3
Order By: Relevance
“…In addition, levels of tyrosine, adenosine, histidine, creatinine, TMP, proline, threonine, cytosine, SDMA, SAH, nicotinamide were consistently altered as the severity of COVID-19 infection progressed, which is consistent with the data on the correlation of tyrosine biosynthesis pathways with the severity of COVID-19 infection 17 [17], as well as the relationship between the severe course of COVID-19 and levels of such amino acids as phenylalanine, proline, valine, valine, glutamate, glutamine, tryptophan, histidine, alanine, leucine, isoleucine, cysteine 18,19 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, levels of tyrosine, adenosine, histidine, creatinine, TMP, proline, threonine, cytosine, SDMA, SAH, nicotinamide were consistently altered as the severity of COVID-19 infection progressed, which is consistent with the data on the correlation of tyrosine biosynthesis pathways with the severity of COVID-19 infection 17 [17], as well as the relationship between the severe course of COVID-19 and levels of such amino acids as phenylalanine, proline, valine, valine, glutamate, glutamine, tryptophan, histidine, alanine, leucine, isoleucine, cysteine 18,19 .…”
Section: Resultssupporting
confidence: 88%
“…COVID-19 can infect human intestinal cells and also replicate in intestinal epithelial cell lines and organoid models of human colon, thus participating in the spread of COVID-19 with increased viremia 20 . A study of differences in plasma amino acid levels between the acute and convalescent stages in people with community-acquired pneumonia showed that plasma levels of arginine and citrulline decreased 19 , which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings demonstrated that saliva presented a similar metabolism shift in plasma [ 32 , 33 ]. Although the dysregulation in COVID-19 patients still needs elucidation, evidence suggests that these amino acid pathways are altered due to the inflammatory response [ 34 ] mediated by biochemical and metabolic pathways related to this disease [ 35 , 36 ]. The change in amino acid rates plays a role in the development of several diseases; metabolomic studies in recent years have shown significant differences in these levels.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic syndrome has been linked to severe outcomes in COVID-19 [2][3][4], and the underlying metabolic changes induced by this massive proinflammatory infection may have ongoing relevance to other acute viral and bacterial respiratory diseases. Previous metabolomics analyses have attempted to identify at-risk individuals by comparing hospitalized patients with COVID-19 to COVID-negative controls who may or may not be hospitalized for other conditions [5][6][7][8]. The few studies that matched our own report relative concentrations [9,10], or metabolite ratios [11].…”
Section: Introductionmentioning
confidence: 99%